Compositional and Symbolic Model-Checking of Real-Time Systems - Larsen, Kim G.; Pettersson, Paul; Yi, Wang (BRICS Report Series, 1996)
Efficient automatic model-checking algorithms for real-time systems have been obtained in recent years based on the state-region graph technique of Alur, Courcoubetis and Dill. However, these algorithms are faced with two potential types of explosion arising from parallel composition: explosion in the space of control nodes, and explosion in the region space over clock variables. In this paper we attack these explosion problems by developing and combining compositional and symbolic model-checking techniques. The presented techniques provide the foundation for a new automatic verification tool Uppaal. Experimental results indicate that Uppaal performs time- and space-wise favorably compared with other real-time verification tools.